2021
DOI: 10.1371/journal.pone.0247931
|View full text |Cite
|
Sign up to set email alerts
|

Could forage peanut in low proportion replace N fertilizer in livestock systems?

Abstract: Palisadegrass [Urochloa brizantha (Hochst. ex A. Rich.) R. D. Webster cv. Marandu] is widely used in Brazil and is typically managed with little or no N fertilizer, which often leads to pasture decline in the long-term. The current relationship between beef price and fertilizer cost in Brazil does not favor fertilizer use in pastures. Legume inclusion is an alternative to adding fertilizer N, but often legumes do not reach a significant proportion (> 30%) in pasture botanical composition. This study evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
(43 reference statements)
0
3
0
1
Order By: Relevance
“…Thus, in pastoral production systems, soil N immobilization is predominant, explaining the decrease in the percentages of dead material with the intensification of the system in which N fertilizer was applied. In fact, a previous study observed that marandu palisadegrass pastures fertilized with N produced higher concentrations of N in the litter (7.9 ± 0.4 g kg −1 organic matter, OM), resulting in a lower C:N ratio (34.0 ± 2.8) than in unfertilized pas-tures (44.1 ± 2.8; [41]), which might have favored the decomposition of dead material by microorganisms.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, in pastoral production systems, soil N immobilization is predominant, explaining the decrease in the percentages of dead material with the intensification of the system in which N fertilizer was applied. In fact, a previous study observed that marandu palisadegrass pastures fertilized with N produced higher concentrations of N in the litter (7.9 ± 0.4 g kg −1 organic matter, OM), resulting in a lower C:N ratio (34.0 ± 2.8) than in unfertilized pas-tures (44.1 ± 2.8; [41]), which might have favored the decomposition of dead material by microorganisms.…”
Section: Discussionmentioning
confidence: 96%
“…ex A. Rich) R. D. Webster] (Longhini et al, 2021). However, forage peanuts provide limited nitrogen fertilization to palisade grass, and the mixed fodder does not reduce enteric methane emissions from crossbred dairy heifers (Berça et al, 2019; Longhini et al, 2021).…”
Section: The Forage Value Of Forage Peanut and Perennial Peanutmentioning
confidence: 99%
“…Thus, it is possible to reduce the use of nitrogen fertilizers, reducing nitrous oxide emissions (Macedo et al 2014). Several studies evaluating intercropping with this legume have shown promising results (Homem et al 2021, Longhini et al 2021, Pereira et al 2020), but there are few studies evaluating pinto peanut under grazing conditions. Despite the potential of intercropped pastures, the use of forage legumes has been decreasing on farms (Emater 2021).…”
Section: Introductionmentioning
confidence: 99%